Life Cycle Cost Analysis Of Buildings (International Journal of Engineering and Computer Science, 2017)
At the time of taking financial decision in construction projects decision maker tempting to think in the short term. In a high construction projects more importance is to place the up-front costs, with less attention to future cost. In order to improve long term decision making life cycle cost analysis is important. Purpose of life cycle cost analysis is to determine cost of project for any number of years. Many times project engineer consider only initial construction cost, with little or no consideration of operation cost, maintenance cost as well as energy cost throughout the life of the building. Life cycle cost analysis (LCCA) method consider initial cost, operation cost, energy cost, maintenance cost, repair cost and residual value to estimate cost effectively. In this paper various economic evaluation methods to calculate life cycle cost (LCC) of building has been discussed and comparison of these methods has been carried out.